Análise dinâmica de estruturas submetidas a forças devidas ao vento - Silva, Lucas Lourenço Ferreira da (Universidade Federal Rural do Semi-Árido, 2018)
As the wind is a nature phenomenon, all the types de building are exposed to its origin dynamic forces, can cause serious accidents or structural damages, being our country one of the that more occur winds of high magnitude. Due to the same it is increasingly developed, it is indispensable the construction of building increasingly high and slender, staying the structures propensity to a greater effect due to action of the wind, either by its tipping or greater displacement in the top of the structure. With this the utilization of software and the method of the finite elements facilitate the process of wind dynamic analyze, through of the calculations of the requests in the structures in able time, because as knows of years ago, the dimensioning of the structures was being made through only of static analyzes, due to principally by inexistence or, to weak capacity of computers in solving the problems more extensive and complexes of dynamic analyze. Being thus, the present study will analyze the results obtained in structure system through of the software SAP2000, as also the verification of the conditions proposals by NBR 6123:1988 – Forças devidas ao vento em edificações, being possible to determinate if the data obtained with the programs can be used in the structures dimensioning. For the analyzes was made the pre-dimensioning of the structures in the building, right after modeled in the program, obtaining as results that the wind speed for the analyze need of speed above of the foreseen by map of the isopleths of the NBR 6123:1988 must use new methods, having as option the method of finites element, as the program SAP 2000 used in this studied, because the use of method simplified of the NBR 6123:1988 does not leads to accurate values; it was found after the frequencies analyze and fundamental periods well minors of the that with the MEF; it stayed highlighted that for a wind of this magnitude the building must be very rigid, sometimes needing a new structural element, for increasing the its rigid and prevent thus the excessive displacements and all the disorder that the same take.
Monografia
Keywords: Rigidez; SAP 2000; NBR 6123:1988; ENGENHARIAS::ENGENHARIA CIVIL